Security awareness in military physical security - Zaharuddin bin Hj Mohammad (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2018)
As Malaysia is developing to become a developed country, its defense system also grows rapidly with increase of personnel and sophisticated equipment and modern weaponry. The effectiveness of the control and protection of all these equipment and weaponry and its installations depends entirely on the level of understanding of the principles of physical security, legal aspects, identification of the threat and the crime and skilled in drawing up a comprehensive protection system for the control and detect any threat. The military installations are usually enforced with the security awareness with initiatives to educate the soldiers, because security awareness programs can not eliminate human weakness and vulnerabilities. The aim of the research is to develop a coping mechanism from the military perspective when dealing with treats. A questionnaire survey was used to study the factors that influence security behaviour among military personnel. It is found that factors such perceived severity, perceived vulnerability, response efficacy, and self-efficacy play important roles in influencing security behaviour. The level of security awareness among military personnel it is high. The recommendation is that the security awareness to increase through campaign, rewards and reviewing standard operating procedure.